In‐hospital outcomes of STEMI patients on warfarin undergoing primary PCI. Issue 1 (30th September 2018) - Marbach, Jeffrey A.; Almufleh, Aws; Bernick, Jordan; Blondeau, Melissa; Osborne, Christina; Russo, Juan; Hibbert, Benjamin; Froeschl, Michael; Labinaz, Marino; Glover, Christopher; Dick, Alexander; So, Derek; et al.
Abstract: Objectives: We sought to describe the safety and efficacy outcomes of patients on warfarin presenting with ST‐elevation myocardial infarction (STEMI). Background: Limited data exist on the outcomes and optimal management of STEMI patients on warfarin undergoing primary percutaneous coronary intervention (PCI). Methods: Baseline characteristics and outcomes were prospectively collected for 2, 390 consecutive STEMI patients referred for primary PCI. Patients were stratified based on warfarin use at baseline. The primary safety endpoint was the rate of in‐hospital bleeding (a composite of major bleeding or minor bleeding) according to the thrombolysis in myocardial infarction (TIMI) classification. Efficacy endpoints included major adverse cardiovascular events (MACE), defined as death, myocardial infarction, or stroke, as well as intracranial bleeding, cardiogenic shock, and length of stay. Multiple logistic regression was used to determine if warfarin was independently associated with bleeding and MACE. Results: Warfarin patients ( n  = 59 vs. n  = 2, 331) were significantly older (73.2 years vs. 61.7 years; P  < 0.01), and more likely to present as Killip Class IV (13.6% vs. 2.7%; P  < 0.01). TIMI major/minor bleeding occurred in 30.4% of the warfarin patients and 14.2% of the control patients ( P  < 0.01). After adjustment warfarin was independently associated with an increased risk of bleeding (OR 2.08; P  = 0.04). Warfarin patients also had an increased frequency of MACE (20.3% vs. 5.9%; P  < 0.01), though this was not significant after adjustment (OR 2.00; P  = 0.10). Conclusions: STEMI patients on warfarin referred for primary PCI are more likely to experience bleeding. New strategies are needed to optimize the management and minimize bleeding in this high‐risk population.